2016
DOI: 10.1007/s00018-016-2148-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of ciliary disassembly

Abstract: As motile organelles and sensors, cilia play pivotal roles in cell physiology, development and organ homeostasis. Ciliary defects are associated with a class of cilia-related diseases or developmental disorders, termed ciliopathies. Even though the presence of cilia is required for diverse functions, cilia can be removed through ciliary shortening or resorption that necessitates disassembly of the cilium, which occurs normally during cell cycle progression, cell differentiation and in response to cellular stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
120
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(121 citation statements)
references
References 154 publications
1
120
0
Order By: Relevance
“…One model is that ciliary length in quiescent cells may determine the G1 duration after cell-cycle reentry [30]. This model is supported by the following observations.…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…One model is that ciliary length in quiescent cells may determine the G1 duration after cell-cycle reentry [30]. This model is supported by the following observations.…”
Section: Introductionsupporting
confidence: 53%
“…The majority of cells begin to retract their primary cilia at the cell-cycle reentry (the G0/G1 transition) [2123, 2730]. Since Tucker et al first reported the reciprocal relationship between ciliation and cell proliferation in cultured cells [27, 28], ciliary absorption (deciliation) has been well analyzed in cell culture [21, 29, 30]. To analyze the deciliation, cultured cells are typically starved of serum and then treated with serum or defined growth factors to induce deciliation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several kinases such as Aurora A, Plk1, and NIMA-related kinases such as Nek1 and Nek2 have been implicated in regulating the stability of cilia (Liang et al., 2016). Nek1 localizes to the basal body region (Shalom et al., 2008), and also to cilia when overexpressed as a kinase dead version (White and Quarmby, 2008).…”
Section: Introductionmentioning
confidence: 99%